NURSES AND PAIN MANAGEMENT IN TERRITORIAL HEALTH EMERGENCIES: A RETROSPECTIVE STUDY - Federico Pecetta; Gian Domenico Giusti; Sara Staffaroni; Matteo Ricci (NSC Nursing)
Introduction: Numerous studies show that the prevalence of pain in pre-hospital emergency setting ranges from 20% to 53%. Additionally, the scientific literature reveals a prevalence of moderate-to-severe pain in 20-64% of patients. According to the latest guidelines, it is essential to ensure proper and effective pain management for all patients experiencing pain. Inadequate pain management can result in complications such as delayed recovery and increased patient distress. In pre-hospital setting, emergency nurses are capable of assessing and treating pain using medications such as fentanyl, ketamine, morphine, NSAIDs and paracetamol. Objective: To evaluate the assessment and treatment of pain by emergency nurses in the pre-hospital setting and assess the potential need for additional training in accordance with the Tuscany region for nurse-staffed ambulances’ analgesia procedure guidelines. Methods: Retrospective study of 4,738 pre-hospital interventions from September 2022 to September 2023. Data were retrieved from EmMaWeb system and included pain assessment using the Numeric Rating Scale (NRS) and administration of analgesics. Results: Pain was assessed at least once in 98.3% of the cases. Moderate to severe pain (NRS ≥ 4) was recorded in 14.2% of the patients. Analgesic drugs were administered in 63.6% of patients with NRS ≥ 4, yet the Tuscany region for nurse-staffed ambulances’ analgesia procedure guidelines was not followed in 36.4% of these cases. 79% of the findings with NRS ≥ 7 (severe pain) received analgesic drug treatment. Paracetamol was the most commonly used analgesic, followed by fentanyl, morphine, and ketamine. Conclusions: Pain assessment practices are well-established in pre-hospital care, but there is still room for improvement in pain management. Pain management does not comply with the Guidelines set by the World Health Organisation and the European Society of Emergency Medicine, a substantial proportion of patients experiencing moderate to severe pain did not receive adequate analgesia. This highlights the need for additional education and training for pre-hospital nurses in pain management and the effective use of analgesic medications to ensure greater adherence to the treatment protocols for nurse-staffed ambulance shared within the Tuscany Region.